METODE PELAKSANAAN KONTRUKSI PEKERJAAN STILLING BASIN WALL RIGHT PADA BANGUNAN PELIMPAH / SPILLWAY - DEDE OMAN SAPUTRA; EKA JULIAR (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
The Cipanas Dam Construction Project, in Pasir Cadasngampar Village, Cibuluh Village, Ujung Jaya District, Sumedang Regency - Indramayu, West Java Province. The stilling basin is used to remove or at least reduce energy in the flow so as not to damage bridge cliffs, roads, buildings and other installations downstream of the spillway building or at the downstream end of the launch channel. The method of implementing the Stilling Basin Work consists of preparing the mobilization of tools, materials, clearing measurements, preparation of work, excavation work and concrete work. casting is divided into layers / segments, for example the WR 27 L1 / layer 1 block is carried out until WR 27 L9 / layer 9.K-125 is the casting implementation on the work floor on blocks WR 27, WR 26, WR 25, WR 24. K-225 is iron installation work. Installation of formwork and waterstop, after the casting is finished, then put the Rubber bend / Contraction Joint.